Gambaran Kemampuan Interaksi Teman Sebaya Dalam Berdiskusi Kelompok Pada Siswa Kelas X SMAN Gondangrejo - Ardea Sri Pramesti; Anniez Rachmawati Musslifah (Pusat Riset dan Inovasi Nasional, 2024)
Students who have good ability to interact tend to be able to adjust to new environments and are comfortable in class. In contrast to students who experience problems in interacting, they tend to have difficulty in adapting so that feelings of pressure arise when in class. As a result, when in group activities or discussions, students tend to be passive, afraid to express their opinions, become quiet when in class, and prefer to do tasks individually. The informants in this study were nine grade X students and one counseling teacher at SMA Negeri Gondangrejo. In this study, researchers used interviews in the form of Focus Group Discussion (FGD), observation and documentation in data collection. The conclusion that can be drawn is that there are two different perspectives related to the phenomenon raised by the researcher. The first is the perspective of informants who have good proximity or ability to interact with their peers. The second is the perspective of informants who have difficulty interacting with their peers.